2022
DOI: 10.1002/cam4.4912
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic dysfunction and obesity‐related cancer: Results from the cross‐sectional National Health and Nutrition Examination Survey

Abstract: Background Metabolic syndrome (MetS), a group of risk factors that define metabolic dysfunction in adults, is strongly associated with obesity and is an emerging risk factor for cancer. However, the association of MetS and degree of metabolic dysfunction with obesity‐related cancer is unknown. Methods Using National Health and Nutrition Examination Survey data from 1999 to 2018, we identified 528 obesity‐related cancer cases and 18,972 cancer‐free participants. MetS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Moreover, in several studies, similar results were reported when a single marker was used to define metabolic health compared with the use of MetS. 36 , 37 , 52 Another limitation of the study includes the small sample size in some subgroup analyses, and the incomplete information on breast cancer subtypes. The observed associations may vary according to breast cancer receptor subtype since a recent study reported a strong positive association between MUOW/OB phenotype and estrogen receptor‐positive breast cancer risk.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, in several studies, similar results were reported when a single marker was used to define metabolic health compared with the use of MetS. 36 , 37 , 52 Another limitation of the study includes the small sample size in some subgroup analyses, and the incomplete information on breast cancer subtypes. The observed associations may vary according to breast cancer receptor subtype since a recent study reported a strong positive association between MUOW/OB phenotype and estrogen receptor‐positive breast cancer risk.…”
Section: Discussionmentioning
confidence: 61%
“…The authors suggest that being metabolically unhealthy as the presence of at least one, two, or three MetS criteria, regardless of BMI category, is associated with a higher risk of at least four cancer types. Moreover, in several studies, similar results were reported when a single marker was used to define metabolic health compared with the use of MetS 36,37,52 . Another limitation of the study includes the small sample size in some subgroup analyses, and the incomplete information on breast cancer subtypes.…”
Section: Discussionmentioning
confidence: 62%
“…Although evidence supporting a relationship between metabolic dysfunction and cancer risk has been increasing, 27–29 the mechanisms are still poorly understood. The most commonly hypothesized mechanism is chronic inflammation resulting from excess adipose tissue, including immune cell infiltration, and cytokine and chemokine release that creates a preneoplastic microenvironment 4,30,31 .…”
Section: Discussionmentioning
confidence: 99%